Polyphenols: Natural food grade biomolecules for treating neurodegenerative diseases from a multi-target perspective - Li, Zhenmin; Zhao, Ting; Shi, Mingqin; Wei, Yuanyuan; Huang, Xiaoyi; Shen, Jiayan; Zhang, Xiaoyu; Xie, Zhaohu; Huang, Peidong; Yuan, Kai; Li, Zhaofu; Li, Ning; et al. (Frontiers in Nutrition, 2023)
As natural functional bioactive ingredients found in foods and plants, polyphenols play various antioxidant and anti-inflammatory roles to prevent the development of disease and restore human health. The multi-target modulation of polyphenols provides a novel practical therapeutic strategy for neurodegenerative diseases that are difficult to treat with traditional drugs like glutathione and cholinesterase inhibitors. This review mainly focuses on the efficacy of polyphenols on ischemic stroke, Parkinson's disease and Alzheimer's disease, including in vitro and in vitro experimental studies. It is further emphasized that polyphenols exert neuroprotective effects primarily through inhibiting production of oxidative stress and inflammatory cytokines, which may be the underlying mechanism. However, polyphenols are still rarely used as medicines to treat neurodegenerative diseases. Due to the lack of clinical trials, the mechanism of polyphenols is still in the stage of insufficient exploration. Future large-scale multi-center randomized controlled trials and in-depth mechanism studies are still needed to fully assess the safety, efficacy and side effects of polyphenols.